2020
DOI: 10.31661/gmj.v9i0.1581
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Dose-Enhancement Effects of Spherical and Rod-Shaped Gold Nanoparticles on the HeLa Cell Line

Abstract: Background: Cervical cancer cells are known as radioresistant cells. Current treatment methods have not improved the patients’ survival efficiently; thus, new therapeutic strategies are needed to enhance the efficacy of radiotherapy. Gold nanomaterials with different shapes and sizes have been explored as radiosensitizers. The present study compared the radiosensitizing effects of gold nanorods (AuNRs) with spherical gold nanoparticles (AuNPs) on the HeLa cell line irradiated with megavoltage X-rays. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The diffusion cell experiments performed with the porcine vaginal mucosa membrane using PET imaging revealed the kinetics of AuNP release from the hydrogel, their accumulation in the membrane, and permeation across it and into the AC. PET is ∼1000 times more sensitive than spectroscopic analytical techniques usually employed for diffusion cell measurements, and it allows a continuous acquisition of a signal for a period of several days. , Overall, the diffusion cell results demonstrated that a very large fraction (47%) of AuNPs accumulated in the membrane after 42 h. This is a very significant result since potential toxicity of AuNPs to the uterus and other healthy tissues should be considered at all steps in the development of future cervical cancer therapies. The gradual liberation of AuNPs from the hydrogel, coupled to their very strong retention at the membrane site, is in agreement with the requirements of AuNP administration locally prior to photothermal and radiosensitization procedures.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The diffusion cell experiments performed with the porcine vaginal mucosa membrane using PET imaging revealed the kinetics of AuNP release from the hydrogel, their accumulation in the membrane, and permeation across it and into the AC. PET is ∼1000 times more sensitive than spectroscopic analytical techniques usually employed for diffusion cell measurements, and it allows a continuous acquisition of a signal for a period of several days. , Overall, the diffusion cell results demonstrated that a very large fraction (47%) of AuNPs accumulated in the membrane after 42 h. This is a very significant result since potential toxicity of AuNPs to the uterus and other healthy tissues should be considered at all steps in the development of future cervical cancer therapies. The gradual liberation of AuNPs from the hydrogel, coupled to their very strong retention at the membrane site, is in agreement with the requirements of AuNP administration locally prior to photothermal and radiosensitization procedures.…”
Section: Discussionmentioning
confidence: 92%
“…Photothermal and brachytherapy applications are being developed for the treatment of cervical cancer that often require the topical administration of therapeutic nanoparticles. In the PTT method, the absorption of light in the visible and near-infrared region by AuNPs leads to local heat generation, which induces damage to cancer cells . In radiotherapy, AuNPs could be used as additives to enhance the effects of radiation on cancer tissues. ,, Moreover, in combination with chemotherapeutics ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…GNPs are very well known for their anticancer properties and tested on various cell lines and especially used on Hela cell lines to decrease their resistance to radiation because of their positive radiosensetizing properties 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Nano-medicine was a new approach for a higher degree of efficacy in treating cancers with least possible side effects 9 . Gold nanoparticles (AuNPs) are considered one of the most dominant systems for many biological applications such as drug delivery and cancer treatment because of their ease in preparation, anti-inflammatory, antioxidant properties, biocompatibility and many possibilities of bio-conjugation 6 .…”
mentioning
confidence: 99%
“…In a comparative study, Amani et al (2020) examined the dose enhancement effect of GNP and GNR on HeLa cells using 6 MV photons. They introduced three concentrations (5, 10, and 15 μg ml −1 ) of these two nanoparticle forms into the cell line and observed that the toxicity of GNRs in HeLa cells was significantly higher than that of GNPs.…”
Section: Introductionmentioning
confidence: 99%